Systemic study for dye decolorization using biosurfactants and biomass - Jamal, Parveen; Munjid, Monawar; Al-Khatib, Ma'an Fahmi Rashid (2013)
Biosorption is becoming a promising alternative to replace or supplement the present dye removal processes which are used for removing dyes from wastewater. In this study, the removal of four dyes; Congo red, Malachite green, Neutral red and Reactive Blue 19, by biosorption using biomass of fungus and bacteria, Panus tigrinus, klebsiella pneumoniae were investigated. Bacterial biosurfactant, obtained from klebsiella pneumonia, was also tested for dye removal. Fungal biomass proved to be the best remover amongst the three bioactive biosurfactant and biomass, which removed 96.948% of Congo red followed by 89.231% removal of Reactive blue 19.